Occurrence of Anthracnose on Welsh Onion Caused by Colletotrichum circinans - Kim, Wan Gyu (The Korean Society of Mycology, 2008)
Anthracnose occurred frequently on leaf sheaths of Welsh onions grown in Gangwha island, Korea in November, 2007. The disease incidence was as high as 30% in five fields investigated. A total of 20 single spore isolates of Colletotrichum species were obtained from the affected plants, and all the isolates were identified as Colletotrichum circinans based on their morphological and cultural characteristics. Three isolates of the fungus caused anthracnose symptoms on the leaf sheaths of Welsh onions by artificial inoculation, which were similar to those observed during the field survey. In this study, the mycological and pathological characteristics of C. circinans identified as causing anthracnose of Welsh onions are clarified.